Neck circumference predicts the incident cardiac events of obese hypertension with obstructive sleep apnea - Xiaoguang Yao; Keming Zhou; Wen Jiang; Mulalibieke Heizhati; Subijiang Tuerxun; Lei Wang (American Journal of Preventive Cardiology, 2025)
Background: Elevated NC has been indicated as a risk factor for hypertensive with obstructive sleep apnea (OSA) in our previous cross-sectional study, but limited data are available regarding the prognostic value of elevated NC and cardiovascular outcome(CVD) in Chinese hypertensives with OSA. Methods: This study included hospitalized hypertensive patients with recorded NC measurements at baseline (2011–2013) by using the data from a large retrospective cohort study (UROSAH Study). Baseline characteristics of the included participants were summarized by the median of NC. The cumulative incidence of cardiac event (CVE) was calculated and the Cox proportional hazards with stepwise models were performed to evaluate the association between NC and CVE. Results: Overall, 3082 participants were categorized into 2 groups according to the median of the baseline NC defined as ≤40 cm (N = 1691) and >40 cm (N = 1391). During a median follow-up of 7.0 years, 211 new-onset CVE occurred. In total cohort, NC>40 cm was associated with a higher risk of new-onset CVE after adjusted confounders [hazard ratio (HR), 1.39, 95 % confidence interval(CI), 1.01–1.93, P = 0.044]. In subgroup analyses, the similar results were observed in patients with age≥60years, OSA, obesity (BMI≥28kg/m2), non-smokers, and eGFR≤90ml/min·1.73m2. Sensitivity analysis showed same result in patients who were not treated with regular CPAP. Conclusion: NC > 40 cm may provide prognostic information for cardiovascular events in hypertensive patients, especially for obese patients and individuals with OSA, suggesting NC >40 cm should be promoted in the risk evaluation of CVD, but the potential mechanism need to explore further.